KALANG, TINJAUAN HISTORIS-ANTROPOLOGIS - Sulistyanto, Bambang (Berkala Arkeologi, 1994)
The terms of â€œkalangâ€ substantially mentioned in Old Javanese inscriptions. Itâ€™s meaning oftenly associated with professions in the timber producing or carpentry. Itâ€™s definition drawn from the existence of "wong Kalang" in the past, it refers to a group of people living on the edge of the forest in several places in Java, as woodcutters or lumberjack. This article will try to discuss the meaning of kalang, through historical-anthropological studies. Accordingly, kalang is not only seen from the definition, instead the study tends to draw a historical frame of kalang as a group of people who continuosly lived from time to time. Hence, these problems cannot be discussed in detail, but some important aspects will be addressed.